Short Communication Audit of Blood Requisition Forms (BRFs) and Their Compliance at a Tertiary Care Hospital of AJ&K - Shaukat, Amnah (International Journal of Pathology, 2021)
Background: Blood Requisition forms are a way of communication between clinicians and the blood bank. Lack of crucial information can lead to disastrous consequences. To achieve Haemovigilance, an audit of current practices is necessary. It enables the transfusion authorities to pinpoint the errors and to rectify them while monitoring progress. The aim of this study was to analyse the practices of clinicians while filling the blood requisition forms in a tertiary care hospital in state of AJK. Materials & Methods: A retrospective descriptive study, was conducted in the blood bank of Divisional Headquarters Teaching Hospital Mirpur AJ&K over a period of two and half months. A total of 2040 forms were analysed for clinicians’ practices while filling blood requisition forms. Twelve categories were made which included name, gender, age, ward, bed number, indication of transfusion, history of blood transfusion, requested blood component, number of units required, nature of request(urgent, immediate, when convenient), date & time of when required and requesting doctor’s name and signature. Results: Out of the 2040 forms, the category name was filled in 100%, age in 73.6%, gender in 56.1%, ward in 95.7%, bed number in 4.7%, provisional diagnosis in 17.4%, history of previous transfusion in 17.1%, blood component required in 66.2%, number of units requested in 75.4%, nature of request in 10.6%, date & time when required in 8.9% and doctor’s name & signature was filled in 96.1% forms. For the forms signed by the requesting doctor only 85.4% had both the name and signature while 14.6% only had the signature. The percentage of completely filled out forms was 0.29% whereas forms having one deficiency were 2.55%, having two deficiencies were 1.62% and those havingmultiple deficiencies were 95.54%. Conclusion: There is huge deficit in this area of practice which can be improved by conducting regular trainings and education of the requesting clinicians by the hospital transfusion committee. Pre and post education status of practices should be closely monitored to achieve Hemovigilance.